2021
DOI: 10.1038/s41598-021-91743-w
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus enhances biofilm formation, aerotolerance, and survival of Campylobacter strains isolated from retail meats

Abstract: In retail meat products, Campylobacter jejuni, C. coli, and Staphylococcus aureus have been reported in high prevalence. The polymicrobial interaction between Campylobacter and other bacteria could enhance Campylobacter survival during the adverse conditions encountered during retail meat processing and storage. This study was designed to investigate the potential role of S. aureus from retail meats in enhancing the survival of Campylobacter exposed to low temperature, aerobic conditions, and biofilm formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Campylobacter has already shown prolonged survival when co-cultured with Pseudomonas spp., allowing it to cope with adverse environmental conditions under normal aerobic conditions [ 25 ]. Similar results were also observed by a few studies that investigated the co-culture of Campylobacter with other protozoa and bacteria under the same conditions, such as Acanthamoeba castellanii , Tetrahymena pyriformis , Staphylococcus aureus and Escherichia coli [ 26 , 27 , 28 , 29 , 30 ]. Moreover, Campylobacter spp.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Campylobacter has already shown prolonged survival when co-cultured with Pseudomonas spp., allowing it to cope with adverse environmental conditions under normal aerobic conditions [ 25 ]. Similar results were also observed by a few studies that investigated the co-culture of Campylobacter with other protozoa and bacteria under the same conditions, such as Acanthamoeba castellanii , Tetrahymena pyriformis , Staphylococcus aureus and Escherichia coli [ 26 , 27 , 28 , 29 , 30 ]. Moreover, Campylobacter spp.…”
Section: Introductionsupporting
confidence: 85%
“…[ 25 ]. Furthermore, a recent study reported the survival of C. jejuni strains in the presence of S. aureus in low-temperature and aerobic conditions, indicating that metabolites produced by S. aureus and the reduced levels of dissolved oxygen improve the survival of C. jejuni [ 30 ]. Additionally, a similar relationship may exist between C. jejuni and Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to monoculture biofilms, the mixed-culture biofilms of C. jejuni with pseudomonads had significantly enhanced mechanical strength [166]. Enhanced biofilm formation was also observed for C. jejuni and C. coli in the presence of S. aureus, with increased aerotolerance and survivability in parallel for the Campylobacter strains [162].…”
Section: Biofilm-forming Ability Of Campylobacter Sppmentioning
confidence: 97%
“…In general, the biofilm-forming ability of Campylobacter is strain-dependent and varies among organism's isolated strains [157,158], as well as between different Campylobacter spp. [159][160][161], while it is also affected by the presence of other bacterial species [162][163][164][165][166][167]. Regarding the biofilm-forming ability of C. jejuni and C. coli, the latter isolates seem able to form biofilms significantly better compared to C. jejuni isolates (p < 0.05) [157,160] and that could be another reason for the increased prevalence of C. coli against C. jejuni in the chicken meat samples.…”
Section: Biofilm-forming Ability Of Campylobacter Sppmentioning
confidence: 99%
“…Microbial species secrete numerous enzymes, signaling and scavenging molecules that can affect the growth and survival of other microbial cells in their vicinity ( Liu et al, 2017 ). Sometimes there are keystone species in a biofilm community which – regardless of their proportion – are often involved in promoting biofilm formation in other species as well as protecting other community members from external stressors ( Parijs and Steenackers, 2018 ; Karki et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%